EFEK BIOLARVISIDA EKSTRAK ETANOL BUAH CITRUS HYSTRIX TERHADAP LARVA AEDES AEGYPTI - Wira Kusuma, I Gusti Ngurah Ananda (Essence of Scientific Medical Journal; Vol 20 No 2 (2022): Volume 20 No. 2 (Juli - Desember 2022) Essential: Essence of Scientific Medical Journal, 2023)
Introduction: Dengue infection is a high-incidence-mosquito-vectored disease that causes various clinical conditions ranging from mild to severe. Eradicating Ae. aegypti mosquito larvae is a common strategy to prevent the spread of dengue infection. This study aims to explore the biolarvicide effect of the ethanol extract of Citrus hystrix fruit on Ae. aegypti larvae. Method: The study was conducted using a bioassay with Ae. aegypti larvae in instars III and IV as samples. The test was divided into 7 groups, namely the control group and the treatment groups at concentrations of 400, 800, 1200, 1600, 2000, and 2400 ppm, each group consisting of 20 larvae, then observed at 1, 24, and 48 hours. Larval mortality was recorded, and data were analyzed to determine the biolarvicide effect, LC50 and LC95 values, and dose-effect relationships. Result: A total of 590 larvae were tested, total mortality was 315 and 418 after 24 and 48 hours, respectively. The one-way ANOVA test resulted in F values of 26.03 and 65.69 (p<0.05) in the periods of 24 and 48 hours, respectively. The R2 values were 0.745 and 0.635 at 24 and 48-hour periods, respectively (p<0.05). The values of LC50 for 24 hours are 989.55 ppm and LC95 for 24 hours are 2785.89 ppm, while LC50 for 48 hours is 483.16 ppm and LC95 for 48 hours is 1555.49 ppm. Conclusion: The authors concluded that the ethanolic extract of Citrus hystrix fruit had a biolarvicidal effect on Ae. aegypti larvae, a linear dose-effect relationship, and a positive, strong, and significant correlation.